Utilization of real time PCR for the assessment of egg burden in the organs of Schistosoma japonicum experimentally infected mice - Moendeg, Kharleezelle J (Archīum Ateneo, 2018)
Schistosoma japonicum, causing zoonotic intestinal schistosomiasis, is found in China, the Philippines and parts of Indonesia. Severe disease manifestations are basically due to the deposition of eggs in some vital organs such as the liver, spleen and brain. Traditionally, histopathological microscopic examination of the egg burden was used to evaluate the intensity of infection in the affected organs. However, this technique is laborious, time-consuming and requires trained personnel. In this study, real time PCR targeting the mitochondrial NADH dehydrogenase I gene was used to compare with microscopic examination of tissue sections in evaluating the egg burdens in different affected organs. Livers, spleens and brains of the S. japonicum infected mice after 8 and 18 weeks post-infection (p.i) were harvested and examined. Results showed that there were statistically significant correlations between the egg burden evaluated by tissue section examination, and the Ct values of the real time PCR of livers with heavy egg burden at 8 (r = −0.81) and 18 (r = −0.80) weeks p.i. Furthermore, a correlation (r = −0.56) between the egg burden assessed by the microscopic examination and Ct value of the real time PCR of spleens with moderate egg burden after 18 weeks p.i and not 8 weeks p.i was also observed. Brains with low egg burden showed no schistosome eggs in the microscopic examination, however one sample tested positive by real time PCR. These results suggested that real time PCR is useful in evaluating schistosome egg burden in the organs of the experimentally infected mice model that will give further insights into the pathology of schistosomiasis.